LAG3-PD-1 Combo Overcome the Disadvantage of Drug Resistance - Wei, Yiming; Li, Zhaoming (Frontiers in Oncology, 2022)
Although PD-1 blockade therapy has been promising in cancer treatment, only a few patients have a positive response to this blockade therapy, as one of its important disadvantages. Therefore, it is important to seek out new targets for cancer immunotherapy to improve the overall response rate in patients. Lymphocyte activation gene-3 (LAG-3), one of the immune-checkpoint receptors members, is mainly expressed in activated immune cells. LAG-3 maintains the body's immune homeostasis under physiological conditions; while mediates the tumor immune escape. Several preclinical and clinical examinations have shown that LAG-3 blockade effectively alleviates the patient’s tolerance of PD-1 immune checkpoint inhibitors. Moreover, it has good clinical efficacy in cancers to combine LAG-3 and PD-1 blocking. Hence, the synchronous LAG-3 and PD-1 inhibition may be a potential new strategy for tumor immunotherapy.